Glyoxal improved functionalization of starch with AZC enhances the hydrophobicity, strength and UV blocking capacities of co-crosslinked polymer. (January 2019) - Ni, Shuzhen; Wang, Baobin; Zhang, Hui; Zhang, Yongchao; Liu, Zhulan; Wu, Weibing; Xiao, Huining; Dai, Hongqi
Graphical abstract: Highlights: A novel approach was developed to modify the starch with glyoxal and AZC together. High hydrophobicity, strength and optical properties were obtained. The enhanced morphology homogeneity was revealed by SEM and AFM imaging. The addition of glyoxal limited the self-polymerization of AZC upon heating. Abstract: An effective and facile approach to functionalize starch was developed using glyoxal and ammonium zirconium carbonate (AZC) as the co-crosslinking agents. The resultant starch was characterized for chemical structure, surface morphology, thermal stability, optical and hydrophobic properties and mechanical strength. 1 H and 13 C nuclear magnetic resonance (NMR) spectrum confirmed the successful Schiff-base reaction on the starch. X-ray diffraction (XRD) showed that the low glyoxal dosage had an adverse impact on the degree of crystallinity. Thermalgravimetric (TG) results revealed the weakened thermal stability at the initial decomposition process and enhanced thermal stability above the maximum degradation temperature. A smoother surface on the resultant film was observed by scanning electron microscopy (SEM) after the addition of glyoxal. Significantly, enhanced mechanical and hydrophobic properties as well as ultraviolet (UV) blocking capacity of the resultant starch film were achieved at 5% (wt) glyoxal and 5% (wt) AZC content. Improved hydrophobic property and mechanical strength were also obtained even with very low dosages of glyoxal (0.5%, wt) and AZC (2.5%, wt). This new type of starch with double functionalities (i.e., hydrophobic and UV blocking capacity) provides beneficial implications for improving the performance of starch-based materials.